Skeletons don't play tubas - Dadey, Debbie; Gurney, John Steven, 1962-; Jones, Marcia Thornton (New York : Scholastic, 1994)
The Bailey School kids are going to find out if the new band teacher could really teach a skeleton to play the tuba.
"A Little Apple paperback.".
4.5
3-6
Keywords: Bands (Music) -- Fiction; Schools -- Fiction; Tuba -- Fiction; Bands (Music) -- Fiction; School stories; Tubas -- Fiction